Effects of Smartphone-based Nutritional Education on the Biochemical Indicators of Patients with Ileostomy - A Khachian; MS Fazeli; H Sabour; H Haghani; GH Akhoondian (Iran University of Medical Sciences, 2019)
Background & Aims: Discharge of materials from ileostomy in a fluid, inconsistent form may lead to water and electrolyte imbalance and decreased nutrient absorption, followed by the risk of malnutrition. The present study aimed to investigate the effects of smartphone-based nutritional education on the biochemical indicators of patients with ileostomy. Materials & Methods: This quasi-experimental clinical trial was conducted with a control group on 72 patients with ileostomy in 2018. The patients were selected via continuous sampling and non-randomly allocated to two groups of intervention and control. After ileostomy implantation, both groups received training on proper dietary habits by the ward staff. In addition, the patients in the intervention group were provided with smartphone-based nutritional education by the researcher. Evaluation of biochemical indicators was performed one day before ileostomy implantation and three weeks after surgery by the researcher. Data were collected using demographic forms and biochemical indicator reports. Data analysis was performed in SPSS version 16 using descriptive and inferential statistics. Results: Before ileostomy implantation, biochemical indicators had no significant differences in the intervention and control groups. Three weeks after ileostomy implantation, the only significant difference was observed in the level of C-reactive protein (CRP), which was significantly higher in the control group compared to the intervention group. Moreover, changes in the biochemical indicators in the study groups before ileostomy implantation and three weeks after the procedure indicated that the levels of albumin and total protein increased more significantly in the intervention group compared to the control group, while the level of CRP increased in the control group. Conclusion: Although statistically significant changes were denoted in the assessed biochemical indicators, the changes were not considered clinically significant and reliable. Therefore, the increasing of time intervals in larger sample populations with more generalizable results could determine the functional role of the training intervention, so that it could be applicable for patients with ileostomy.